2020
DOI: 10.1093/jee/toaa075
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Current Tarnished Plant Bug (Hemiptera: Miridae) Thresholds in Transgenic MON 88702 Cotton Expressing the Bt Cry51Aa2.834_16 Trait

Abstract: The tarnished plant bug, Lygus lineolaris (Palisot de Beauvois), is an important pest of cotton in many areas of the southern United States. An experiment was conducted at two locations in Mississippi during 2016 and 2017 to evaluate action thresholds for tarnished plant bug on a novel Bacillus thuringiensis cotton that expresses the Cry51Aa2.834_16 toxin. Treatments included the current action threshold, a 2× threshold, and treatments where insecticides were only applied during the early season (preflower) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 20 publications
(21 reference statements)
3
8
0
Order By: Relevance
“…The lack of an effective pheromone has severely limited the utility of ecological studies evaluating the movement of Lygus in the landscape and future research should focus on this aspect of their biology. Transgenic cotton varieties expressing insecticidal proteins have reduced the number of pesticide applications required for control of L. lineolaris in Thryvon cotton (Cry51Aa2.834_16) compared to non-Thryvon cotton [ 161 , 162 ]. Bt cotton expressing these Cry proteins need to be tested further to establish their action thresholds for Lygus management before releasing them to cotton growers for large scale cultivation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The lack of an effective pheromone has severely limited the utility of ecological studies evaluating the movement of Lygus in the landscape and future research should focus on this aspect of their biology. Transgenic cotton varieties expressing insecticidal proteins have reduced the number of pesticide applications required for control of L. lineolaris in Thryvon cotton (Cry51Aa2.834_16) compared to non-Thryvon cotton [ 161 , 162 ]. Bt cotton expressing these Cry proteins need to be tested further to establish their action thresholds for Lygus management before releasing them to cotton growers for large scale cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies with transformed plants expressing the TIC807 protein reported 35% to 78% mortality of newly eclosed L. hesperus nymphs in the laboratory [ 160 ], but no such studies have been published on L. lineolaris . Field experiments have shown a reduction in the number of sprays needed for L. lineolaris management in Thryvon cotton compared to non-Thryvon cotton [ 161 , 162 ]. Graham and Stewart [ 161 ] observed a reduction of 1.25 insecticide sprays for L. lineolaris in Thryvon cotton compared to a near isogenic non-Thryvon cotton variety when sprays were made based on the current action threshold.…”
Section: Integrated Management Strategiesmentioning
confidence: 99%
See 3 more Smart Citations